Discovery of Inhibitors for Mycobacterium Tuberculosis Peptide Deformylase Based on Virtual Screening in Silico. Issue 3 (27th October 2021) - Li, Xinpeng; Jiang, Qihua; Yang, Xiaolan
Abstract: Tuberculosis has been the serious disease threatening human health and public safety due to the emergence of MDR and XDR‐TB. Mycobacterium tuberculosis peptide deformylase ( Mt PDF) is a valuable target for antituberculotics. In order to discover new potential inhibitor candidates of Mt PDF as leads for antituberculotics, Discovery Studio (DS) 2019 was used to perform molecular docking for virtual screening in silico with the bioactive compound library‐I (L1700) against Mt PDF. Six compounds with high docking scores and favourable ligand‐protein interactions by LibDock and CDOCKER were selected for the evaluation of the inhibition potencies against Mt PDF and Mycobacterium smegmatis . GST‐6×His tagged Mt PDF was recombinant expressed and purified firstly by Glutathione Sepharose 4B, and secondly by Ni Sepharose 6 FF after the cleavage of human rhinovirus 3C protease. These compounds showed IC50 values from 0.5 μmol/L to 112 μmol/L against Mt PDF, among which CUDC‐101 bearing hydroxamic acid exhibited IC50 of 0.5 μmol/L on Mt PDF and MIC against Mycobacterium smegmatis of 32 μg/mL, and Ixazomib Citrate with IC50 of 63 μmol/L and MIC of 16 μg/mL. CUDC‐101 and Ixazomib Citrate are promising as the potential leads for antituberculotics. Abstract :